Performance and Apparent Digestibility of Broiler Starter Fed Diets Containing Gliricidia Sepium Leaf Meal - O.D., Oloruntola; S.O., Ayodele; J.O., Agbede; E.K., Asaniyan (Asian Journal of Biological and Life Sciences, 2016)
One hundred and forty four (144) day old broiler chicks were used to determine the effect of Gliricidia sepium leaf meal (GLM) on performance and apparent digestibility of broiler starter. A basal diet (0 g/kg GLM) was formulated for the starter phase to meet the requirements of the broiler chicks. Thereafter, two diets were formulated to contain GLM at 50 and 100 g/kg respectively. The birds were arranged in a completely randomized design having three treatments with each replicate having sixteen chicks. The birds were fed ad libitum with their respective diets for 28 days. The final live weight of birds on the control (796g/bird vs 746 – 670 g/bird) and total weight gain (758 g/bird vs 708– 662 g/bird) decreased with increased GLM inclusion in the diets while the total feed intake, protein intake and feed conversion ratio were similarly affected by the dietary treatments. The apparent crude protein digestibility of birds fed the control diet and diet containing 50 g/kg GLM were similar but higher than those fed diet containing 100g/kg GLM. The apparent ash digestibility of birds fed on 50 g/kg GLM containing diet (70.78%) was higher than those fed the control, and diet containing 100 g/kg GLM. It could be concluded that GLM at 50 g/kg inclusion level in diet of broiler starter may be the optimum inclusion level.
Keywords: Broiler starter; digestibility; Gliricidia sepium leaf meal